1999
DOI: 10.1046/j.1440-1681.1999.03155.x
|View full text |Cite
|
Sign up to set email alerts
|

Foetal Fluid Balance and Hormone Status Following Nephrectomy in the Foetal Sheep

Abstract: 1. The role of the kidneys in the maintenance of normal foetal plasma (FP) composition and hormone concentrations was examined in the present study. Five ovine foetuses were chronically cannulated and nephrectomized (nephx) at 100 +/- 1 days of gestation and maintained for 14 days. These were compared to five intact control foetuses. 2. Four hours after nephx, FP renin concentrations were significantly lower than in control foetuses. By 48 h, renin concentrations in nephx foetuses were below the level of detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Data have already been cited about how circulating calcitriol levels are low in fetal rats but increased in fetal sheep. As already noted, fetal nephrectomy in lambs reduced the serum calcitriol level by 60% and was accompanied by a fall in serum calcium and an increase in serum phosphorus in one study (455), but serum calcium remained normal in another study of nephrectomized fetal lambs (459), and serum calcium and phosphorus were normal in nephrectomized fetal rats (105). The investigators in the first study assumed that loss of renal production of calcitriol caused the hypocalcemia and hyperphosphatemia and were able to show that pharmacological treatment with calcitriol reversed these abnormalities (455).…”
Section: Animal Datasupporting
confidence: 56%
See 1 more Smart Citation
“…Data have already been cited about how circulating calcitriol levels are low in fetal rats but increased in fetal sheep. As already noted, fetal nephrectomy in lambs reduced the serum calcitriol level by 60% and was accompanied by a fall in serum calcium and an increase in serum phosphorus in one study (455), but serum calcium remained normal in another study of nephrectomized fetal lambs (459), and serum calcium and phosphorus were normal in nephrectomized fetal rats (105). The investigators in the first study assumed that loss of renal production of calcitriol caused the hypocalcemia and hyperphosphatemia and were able to show that pharmacological treatment with calcitriol reversed these abnormalities (455).…”
Section: Animal Datasupporting
confidence: 56%
“…The investigators concluded that loss of renal 1␣-hydroxylase and production of calcitriol resulted in altered fetal mineral homeostasis, rather than the loss of renal function to reabsorb and excrete minerals. However, other investigators performed bilateral nephrectomy in fetal lambs and observed an increase in serum phosphorus, no change in serum calcium, and a nonsignificant reduction in the excretion of calcium into the amniotic fluid and allantois (459). Bilateral nephrectomy in fetal rats did not alter the serum calcium or phosphorus either; calcitriol and PTH were not measured in those experiments (105).…”
Section: Animal Datamentioning
confidence: 86%
“…Merino ewes carrying fetuses of known gestational age underwent uni‐x or sham surgery at 100 days postconception, as previously described (uni‐x, n = 7; sham n = 7) (Moritz et al. ). Only female fetuses were selected for use in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Merino ewes carrying female fetuses of known gestational age underwent surgery at 100 days post-conception, as described previously [20], [27]. The left renal artery, vein and ureter were ligated and the kidney was cleared from the surrounding fat (uni-x group, n = 7).…”
Section: Methodsmentioning
confidence: 99%